An evaluation of the impact of diversification on financial perfomance at Telone - Chipura, Chipura Shelton (Midlands State University, 2017)
The main objective of this project was to determine the impact of diversification on financial performance, so as toenhance the effective implementation of the diversification strategy. The central issue that gave rise to this research is the increased attention and growing popularity of diversification among Zimbabwean companies. This study adopted the descriptive research methodology to answer the research questions which were both qualitative and quantitative in nature. Both primary and secondary sources of data were used in this study with the aid of eviews8 and stata11 packages to determine relationships between the variables under review. The variables included diversification as an independent variable and operating costs as well as operating profit as dependent variables. The research key findings show that diversification positively impactsoperating cost by 49% and profitability by 66% at TelOne. From questionnaire and interview data analysis, it has been found that the benefits of diversification outweigh its costs. Collective marketing and continuous product analysis were considered to be best practices in diversification. The researcher recommended the company to engage cost cutting measures to minimize the costs posed by diversification and to improve its profit margins. Collective marketing and selling of the company’s services was also recommended by the researcher as it enables the company to enjoy marketing economies of scope. The company has also been advised to use internally generated funds to finance diversification strategy as that minimizes loss of collateral security and risks related to changes in interest rates.